PERANAN HEART RATE TERHADAP KUALITAS CITRA PENGGUNAAN â€œCOVID-19â€ WINDOW UNTUK PEMERIKSAAN CT-SCAN THORAX POLOS PADA PASIEN SUSPEK COVID-19 - Mayasari, Anisa (JRI (Jurnal Radiografer Indonesia), 2020)
Background: Non-contrast chest CT-Scan is one of the COVID-19 screening methods. At Panti Waluyo hospital of Surakarta, Non-contrast chest CT-Scan did not use the HRCT technique, low-dose technique, Lung Window, and Mediastinum Window, but used a standard-dose technique and â€œCOVID-19â€ window. Methods: The research was conducted at Panti Waluyo hospital of Surakarta, scanning process using GE Brightspeed 8 Slices CT-Scan. The position of the patient is supine feet first, the midline is at the midsagittal plane and axillary line, the scanning process begins with a vertical and horizontal scout photo, scanning area from Thoracal 1st to lumbar 3rd, using a helical scan, and â€œCOVID-19â€ window with 120 kV, 100 mA, 0.8 s, 5 mm slice thickness, FoV 34 cm, gantry tilt 0 Â°, reconstruction 1.25 mm, pitch 1.35: 1, window width 1600, and window level -250. Results: The expertise of Radiologists indicates bilateral pneumonia (typical COVID-19). The "COVID-19" window presents GGO and clarifies the difference between GGO and lung consolidation. It shows the contour of the heart and part of the liver, without adding another window. So, it can increase the effectiveness of time and radiological film. Conclusions: For non-contrast chest CT-scan in patients with suspected COVID-19, it is better to use the â€œCOVID-19â€ window than the lung or mediastinal window.